Surface application of limestone and calcium-magnesium silicate in a tropical no-tillage system - Castro, G. S.A.; Crusciol, C. A.C. [UNESP]; da Costa, C. H.M.; Ferrari Neto, J. [UNESP]; Mancuso, M. A.C. [UNESP] (Springer Nature, 2016)
Although lime is currently the most commonly applied material for soil acidity correction in Brazil, calcium-magnesium silicate application may efficiently replace this source due to its higher solubility and silicon supply, which is beneficial for plant development. This study aimed to evaluate the efficiency of surface liming and silicate application on soil chemical attributes as well as soybean and maize nutrition, yield components, and grain yield. The experiment was conducted in a Rhodic Hapludox in Botucatu-SP, Brazil. The randomized complete block design contained 16 replications. Treatments consisted of two materials for soil acidity correction (dolomitic lime, calcium/magnesium silicate), applied on October 2006 to raise base saturation up to 70%, and a control, with no acidity correction. Soybean and maize were sown in 2006/2007 and 2007/2008, respectively. After 18 months Ca-Mg silicate corrected soil acidity up to 0.60 m, and increased exchangeable base levels up to 0.40 m. Silicate increased silicon concentrations in plant tissues in both crops as well as phosphorus in soybean. The application of both sources increased calcium and magnesium concentrations as well as yield components and yield grains of soybean and maize. Soil acidity correction improved the efficiency of fertilizers applied for grain production.
Keywords: Acid soils; Annual crops; Brazilian ‘cerrado’; Liming